A weighted logarithmic barrier interior-point method for linearly constrained optimization - LAMRI, Selma; MERIKHI, Bachir; ACHACHE, Mohamed (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
In this paper, a weighted logarithmic barrier interior-point method for solving the linearly convex constrained optimization problems is presented. Unlike the classical central-path, the barrier parameter associated with the perturbed barrier problems, is not a scalar but is a weighted positive vector. This modification gives a theoretical flexibility on its convergence and its numerical performance. In addition, this method is of a Newton descent direction and the computation of the step-size along this direction is based on a new efficient technique called the tangent method. The practical efficiency of our approach is shown by giving some numerical results. Mathematics Subject Classification (2010): 90C30, 90C25, 90C51.